Status Resistensi Larva Aedes aegypti (Linnaeus) terhadap Temephos (Studi di Kelurahan Jatiasih Kecamatan Jatiasih Kota Bekasi Provinsi Jawa Barat) - Lasrika S. Sinaga; Martini Martini; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Larvacides temephos has long been used in vector control of DHF Ae. aegypti. The use of insecticides for a long time and continuously can increase the incidence of insecticide resistance. The aim of this research is to determine the resistance status of Ae. aegypti in Jatiasih Village to temephos. This research includes the study of pure experimentation (True Experiment) to posttest design with control group (Only posttest control group design) with a sample of Ae.aegyptiinstar III and instar IV larval rearing the results of the first generation of larvae survey results. The results showed the percentage of larval mortality Ae. aegypti of Village Jatiasih to temephos by using a concentration of 0.0025 mg/l; 0.005 mg/l; 0.01 mg/l; 0.02 mg/l; 0.04 mg/l and 0.08 mg/l. According to WHO’s recommended concentration category of 0,02 mg/l showed that village Jatiasih is still susceptible to temephos with the death of Ae. aegypti by 98%. The analysis of the data was tested by using Kruskal Wallis test and Mann Whitney Test to determine the differences in each concentration. Kruskal Wallis test was obtained on the value of 0.001 (p